2012
DOI: 10.2139/ssrn.2102726
|View full text |Cite
|
Sign up to set email alerts
|

The Negative Consequences of Overambitious Curricula in Developing Countries

Abstract: Learning profiles that track changes in student skills per year of schooling often find shockingly low learning gains. Using data from three recent studies in South Asia and Africa, we show that a majority of students spend years of instruction with no progress on basics. We argue shallow learning profiles are in part the result of curricular paces moving much faster than the pace of learning. To demonstrate the consequences of a gap between the curriculum and student mastery, we construct a simple, formal mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 32 publications
(16 reference statements)
2
27
0
Order By: Relevance
“…To summarize, we observed that some learning takes place in all schools, even in low-output schools, but not all students are learning the curriculum material and those who are too far behind do not seem to catch up. These findings are consistent with the hypothesis put forward by Pritchett and Beatty (2012), which was that students who are on track or not too far behind are learning, and those who were behind stay behind.…”
Section: The Bottom Panel Ofsupporting
confidence: 91%
“…To summarize, we observed that some learning takes place in all schools, even in low-output schools, but not all students are learning the curriculum material and those who are too far behind do not seem to catch up. These findings are consistent with the hypothesis put forward by Pritchett and Beatty (2012), which was that students who are on track or not too far behind are learning, and those who were behind stay behind.…”
Section: The Bottom Panel Ofsupporting
confidence: 91%
“…This explanation is consistent with that given byPritchett and Beatty (2012), who argue that the slow pace of learning evident in a number of developing countries is the result of reliance on overly ambitious curricula.10 This paper builds on a growing literature that combines structural estimation with randomized controlled experiments (seeTodd and Wolpin [2006] and the citations within).…”
supporting
confidence: 71%
“…Both Pritchett and Beatty (2012) and Banerjee and Duflo (2011) have identified that students in developing countries have large learning deficits. They show that even children with relatively high levels of educational attainment often have very few cognitive skills to show for all their years of schooling.…”
Section: Introductionmentioning
confidence: 99%